Model Sistem Dinamik dalam Simulasi dan Evaluasi Penanganan Sampah di Kota Medan - Ade Andreas Sinabariba; Enriko Vincentius Manurung; Putri Harliana (Piston: Jurnal Teknologi, 2025)
Waste management is a significant challenge for the rapidly growing city of Medan. This study aims to develop a dynamic system model for simulating and evaluating waste management in Medan. The model is used to analyze the impact of various waste management policies on the amount of waste processed, the required waste management facilities, and the associated costs. The simulation results show that the model can predict population growth with high accuracy (MAPE 1.48%) and waste generation with good accuracy (MAPE 3.30%). Additionally, the simulation reveals an increasing need for waste trucks in line with population growth and waste generation. The contribution of this study is the development of a dynamic system model that can be used to plan more efficient and sustainable waste management policies in the future. However, this study also has some limitations, such as significant deviations in the waste generation predictions for 2024, influenced by external factors that are difficult to predict, such as changes in public behavior and new policies. Alternative solutions for future research include the development of a more complex model that accounts for external variables such as new waste management policies, public awareness, and other environmental factors. Overall, this study demonstrates that the dynamic system model can be an effective tool for planning more efficient waste management policies in Medan, with useful results for sustainable waste management policy planning.